The significance of participation in capacity development and project sustainability: a case study of the Zimbabwe Secondary Teacher Training Environmental Education Project (St²eep) - Van Ongevalle, Jan (Rhodes University, Faculty of Education, Department of Education, 2007)
This study uses a systems thinking perspective to explore the role and meaning of participation, capacity development and project sustainability in the Zimbabwe Secondary Teacher Training Environmental Education Project (St²eep). Since there was no consistent critical reflection upon the different assumptions that underpin these important aspects of St²eep in the original project design, this study aims to articulate a theoretical framework for guiding the project. St2eep is a donorfunded project, located in the Ministry of Higher and Tertiary Education in Zimbabwe that seeks to integrate environmental education across the curriculum of secondary teacher education. The study first develops a theoretical framework drawing on systems thinking. In particular it uses the holistic and constructivist perspectives embedded in systems thinking to describe a number of analytic frameworks that are used as a guide to investigate participation, capacity development and project sustainability in the St²eep case study. The research methodology comprises a qualitative case study approach, which contains elements of an instrumental, evaluative and critical case study. Data-collection methods include document analysis, focus group discussions, focus group interviews, semi-structured face-to-face interviews and participant observation. Data analysis follows the constant comparative method of coding and categorising data as outlined by Strauss and Corbin (1998). The outcomes of this research show that participation processes in St²eep evolve around the interactions between a political dimension and a learning dimension. The political dimension relates to giving the project stakeholders a critical voice, allowing them to shape the project and involving them in the decision-making process. This approach has fostered an ongoing learning process in a small team of committed stakeholders based on the principles of collaborative learning, team learning and action research. Participation was shown to enhance capacity-development processes at individual and institutional level by the provision of support through learning teams, and by the renegotiation of responsibilities and power relations between lecturers involved in St²eep, donor representatives and college administrations. The strong operational role of the donor organisation was seen as a serious threat towards individual and institutional capacity development since it creates a functional but artificial and independent project system within the college system and takes over any local institutional support structure that it might seek to develop. Fostering continuous learning and capacity development, St²eep's participatory approach was shown to contribute to a better understanding of the interconnectedness of factors that influence future sustainability of the project and the implementation of environmental education. This has assisted in the development of different scenarios on the sustainability of the project. The research shows that the project-ustainability planning process draws directly from St²eep's ongoing learning process, with individual and institutional capacity development featuring strongly in the different scenarios, and with the external context such as the economic situation and the low priority of environmental education being recognised as important factors that need to be considered. Drawing on the findings from the case study, this study makes a tentative recommendation that donor organisations should focus more on capacity-development initiatives and avoid taking on a strong operational role in project activities. The research also recommends that there is need for a deliberate focus on both the political and learning dimensions of the participation process in order to foster local ownership. Making the learning aspect much more central in St²eep is presented as a possible strategy for motivating a larger number of college lecturers to become involved in the project and the implementation of environmental education. The study also urges St²eep to combine the different scenarios that have emerged during the project sustainability planning process and to focus on the benefits that stakeholders want to see sustained.
Keywords: High school teachers -- Training of -- Zimbabwe; Environmental education -- Study and teaching (secondary) -- Zimbabwe; Environmental education -- Curricula -- Case studies -- Zimbabwe; Environmental education -- Curricula -- Zimbabwe